2021
DOI: 10.1186/s12933-021-01377-5
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between the ratio of triglycerides to high-density lipoprotein cholesterol and diabetes incidence in Korean adults

Abstract: Background Insulin resistance is associated with the incidence of diabetes and cardiovascular diseases such as myocardial infarction. The ratio of triglycerides (TG) to high-density lipoprotein cholesterol (HDL-C) (TG/HDL-C ratio) is positively correlated with insulin resistance. This study aimed to investigate the relationship between the TG/HDL-C ratio and the incidence of diabetes in Korean adults. Methods This retrospective study used data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 55 publications
1
15
2
Order By: Relevance
“…The results of the triglycerides level test showed an increase in the mean among diabetics groups in compared with the control group, interestingly that the most increase was in males. Except mean TG level in diabetic women without overweight, the Comparison of the findings with those of other studies confirms Increased TG level was associated with a diabetic risk in both sexes (27). In the healthy group, we notice an increase in the level of females compared to men, these findings of the current study do not support the previous research that suggests in young adulthood, men tend to have higher triglyceride levels than women (28).…”
Section: Discussioncontrasting
confidence: 95%
“…The results of the triglycerides level test showed an increase in the mean among diabetics groups in compared with the control group, interestingly that the most increase was in males. Except mean TG level in diabetic women without overweight, the Comparison of the findings with those of other studies confirms Increased TG level was associated with a diabetic risk in both sexes (27). In the healthy group, we notice an increase in the level of females compared to men, these findings of the current study do not support the previous research that suggests in young adulthood, men tend to have higher triglyceride levels than women (28).…”
Section: Discussioncontrasting
confidence: 95%
“…Also, the anabolism is significantly lower in the elderly compared to middle-aged-onset patients. Elderly-onset T2DM patients have relatively preserved β-cell function and higher IR [ 14 ]. In addition, the relationship between alcohol consumption and IR T2DM remains controversial [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the TG/HDL-C has been recognized as a potential predictive marker of insulin resistance (IR), which is a key trigger for the development of T2DM. Increased TG/HDL-C ratios have been shown to indicate a greater risk of new-onset T2DM in some studies [ 14 ]. Additionally, past studies have extensively explored sex-specific cutoff points for TG/HDL-C, which classify participants as high or low IR and cardiovascular disease (CVD) risk [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A molecular lipid analysis showed that plasma TG levels were the only variable associated with DM in high-risk groups [8], and a high-fat diet increased the synthesis of TG in the liver, reduced relative high-density lipoprotein cholesterol (HDL-C), and accelerated the onset of DM [9]. In population cohort studies, a higher TG-related indicators were associated with DM independent of insulin resistance, highlighting the importance of TRLs in the development of DM [10][11][12].…”
Section: Introductionmentioning
confidence: 99%